Effect of Straw and Wood Ash on Soil Carbon Sequestration and Bacterial Community in a Calcareous Soil - Zhao, Huili; Ahmad, Shakeel; Wu, Nan; Suo, Lizhu; Tian, Xiaohong; Zhao, Ying; Yu, Jinyi; Wang, Li; Si, Bingcheng (Frontiers in Microbiology, 2022)
Soil fertility can be improved by effectively utilizing agricultural waste. Straw can supply energy and wood ash adds nutrients to improve soil quality. However, few kinds of research have investigated the effect of wood ash and straw on soil carbon sequestration and the soil bacterial population, particularly in calcareous soils. The main goal of this current study was to quantify the impact of a combination of wood ash and straw on the indicators described above using stable δ13C isotope analyses by applying wheat straw to calcareous soil under a long-term C4 crop rotation. The incubation experiment included four treatments as follows: (i) no amendment (Control); (ii) amendment with wood ash (W); (iii) amendment with straw (S); and (iv) a combined amendment of straw and wood ash (SW). Our results showed that sequestration of soil inorganic carbon (SIC) in the SW and W treatments was higher (an average of 7.78%) than that in the S and Control treatments. The sequestered soil organic carbon (SOC) in the SW treatment was 1.25-fold greater than that in the S treatment, while there was no evident effect on the SOC content compared with straw alone. The microbial biomass carbon increased under SW by 143.33%, S by 102.23%, and W by 13.89% relative to control. The dissolved organic carbon increased under SW by 112.0%, S by 66.61%, and W by 37.33% relative to the control. The pH and electrical conductivity were higher in the SW and W treatments than in the S treatment and the control. The SW was conducive to maintaining soil enzymatic activities and bacterial diversity. Bacteroidetes and Actinobacteriota were dominant in SW, while the Acidobacteria phyla were dominant in the S treatment. The diversity of bacteria in the soil and community composition of the bacteria were predominantly assessed by the levels of water-soluble K, pH, and electrical conductivity. The incorporation of straw and wood ash is probably more effective at improving SIC and SOC sequestration and ameliorates the soil microhabitat.